Aerial Imagery Reveals Abnormal Stingray, Taeniura lymma (Myliobatiformes: Dasyatidae), in the Central Red Sea - Ioana Andreea Ciocănaru; Brian Owain Nieuwenhuis; Raquel Lubambo Ostrovski; Jesse E. M. Cochran; Ashlie J. McIvor; Burton H. Jones (Ecology and Evolution)
ABSTRACT While morphological abnormalities have been widely reported in batomorphs, ontogenetic deformities of the posterior pectoral fin are rare. In this paper, we present a bluespotted ribbontail ray, Taeniura lymma (Forsskål, 1775), with symmetrically deformed posterior pectoral fins. The specimen was observed through aerial imagery on a coastal sandflat in the central Red Sea (22.30° N, 39.09° E). The bilateral symmetry of the deformity indicates it likely has a genetic base. However, lacking access to the specimen, the ultimate cause of the abnormality remains uncertain. The incomplete disk closure did not seem to affect survival, as the specimen reached a disk width of 22 cm, well above the regional size at sexual maturity. Our observations constitute both the first report of a morphological abnormality in T. lymma and the first record of a batomorph with a symmetrically deformed posterior pectoral fin. In this paper, we present a bluespotted ribbontail ray, Taeniura lymma (Forsskål, 1775), with symmetrically deformed posterior pectoral fins. The specimen was observed through aerial imagery on a coastal sandflat in the central Red Sea (22.30° N, 39.09° E). Our observations constitute both the first report of a morphological abnormality in T. lymma and the first record of a batomorph with a symmetrically deformed posterior pectoral fin.